Subjective memory complaints, depressive symptoms and cognition in Parkinson's disease patients. (9th June 2014) - Lehrner, J.; Moser, D.; Klug, S.; Gleiß, A.; Auff, E.; Pirker, W.; Pusswald, G.
<x xml:space="preserve">Abstract</x> Background and purpose The goal of this study was to establish the prevalence of subjective memory complaints (SMCs) and depressive symptoms (DS)s and their relation to cognitive functioning in patients with Parkinson's disease (PD). Methods In all, 248 controls and 104 PD patients were included in the study. The PD group was subdivided into three PD subtypes with mild cognitive impairment (MCI) according to the Petersen criteria and three PD subtypes with MCI according to the Litvan criteria. Results Substantial SMCs were reported by 7.7% of controls and 16.3% of the PD patients (P < 0.001). A clinically relevant degree of DSs was evident in 16.6% of controls compared with 40.4% in the PD group (P < 0.001). An analysis of variance revealed a statistically significant difference for SMCs across all Petersen groups as well across all Litvan groups. Two‐factor analyses of variance with the factors cognitive status (MCI subtype) and depressive state (depressed versus not depressed) and SMCs as dependent variable revealed significant results. Conclusions Approximately 15% of PD patients seeking help in a movement disorder clinic report significant SMCs, with an increasing degree from cognitively healthy PD to PD‐MCI. Significant DSs increase SMCs across all cognitive status groups.